Assessment of 1, 25-dihydroxyvitamin D3 effects on Treg cells in a mouse model of systemic lupus erythematosus. (February 2015) - Lavi Arab, Fahimeh; Rastin, Maryam; Faraji, Fatemeh; Zamani Taghizadeh Rabe, Shahrzad; Tabasi, Nafise; Khazaee, Mahdieh; Haghmorad, Dariush; Mahmoudi, Mahmoud
Abstract Context: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease which is characterized by the presence of auto-reactive T cell and anti-ds DNA antibodies. Treg cells are crucial for maintaining immunologic self-tolerance and are shown to be reduced in SLE patients. 1, 25-Dihydroxyvitamin D3 has immunomedulatory effects on the immune system and has recently received substantial attention. Objective: In this study we evaluated the effects of 1, 25-dihydroxyvitamin D3 on Treg cells and related cytokines in lupus-like induced mice model. Materials and methods: Female Balb/c mice were divided into four groups: Group one: injected with PBS and Freund's adjuvant; Group two: injected with non-activated chromatin; Group three: Lupus-like disease was induced with activated chromatin; Group four: Mice were initially treated for two weeks with 1, 25-dihydroxyvitamin D3 and then lupus-like disease was induced. Group five: Four mice from group one were treated with 1, 25-dihydroxyvitamin D3 for two weeks after disease establishment. Ten weeks after the last injection the mice were killed and spleens were studied for Treg percentages and expression of cytokine genes. Results: We found that treatment with 1, 25-dihydroxyvitamin D3 reduces IL-6 and IL-10 mRNA expression and increases TGF-β and Foxp3 mRNA expression levels, and also enhances spleen Treg percentage. Conclusions: The remarkable reduction of IL-6 and IL-10 gene expressions, significant enhancement of TGF-β and Foxp3 gene expressions, along with an increase in Treg cell population after oral 1, 25-dihydroxyvitamin D3 administration suggest a possible role for this vitamin as a prophylactic supplement in SLE.